Analysis of the Influence of Employee Empowerment, Motivation, and Job Satisfaction on the Performance of Members of the Narcotics Division, Central Java Regional Police - Hapsari, Pamungkas; Wijayanto, Yeremia; Ardoko, Prono (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2025)
This study aims to examine and analyze the effect of employee empowerment on the performance of members of the Narcotics Division, Central Java Regional Police. It also seeks to explore the impact of motivation and job satisfaction on the performance of the same members, as well as the combined effect of employee empowerment, motivation, and job satisfaction on their performance. The research method used is a quantitative approach, with data collected through questionnaires. The questionnaire is a data collection tool in which a list of questions/statements is distributed to respondents in order to obtain their responses. The analysis results show that employee empowerment does not significantly affect the performance of members of the Narcotics Division, Central Java Regional Police. Motivation has a significant effect on the performance of the members, and job satisfaction also significantly influences their performance. Together, the variables of empowerment, motivation, and job satisfaction significantly affect the performance of members of the Narcotics Division, Central Java Regional Police.